2020
DOI: 10.3389/fimmu.2020.01407
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Effect of Polyphenols for Colorectal Cancer

Abstract: Colorectal cancer (CRC) is one of the most prevalent cancers that threaten people in many countries. It is a multi-factorial chronic disease caused by a combination of genetic and environmental factors, but it is mainly related to lifestyle factors, including diet. Plentiful plant foods and beverages are abundant in polyphenols with antioxidant, anti-atherosclerotic, anti-inflammatory, and anticancer properties. These compounds participate in host nutrition and disease pathology regulation in different ways. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 105 publications
1
36
0
1
Order By: Relevance
“…The same proves true for other dietary components, such as polyphenols [ 113 ] vitamins [ 114 , 115 , 116 ], and minerals [ 116 , 117 ] alone or in combination.…”
Section: Nutrients Epigenetics and Colorectal Cancermentioning
confidence: 72%
“…The same proves true for other dietary components, such as polyphenols [ 113 ] vitamins [ 114 , 115 , 116 ], and minerals [ 116 , 117 ] alone or in combination.…”
Section: Nutrients Epigenetics and Colorectal Cancermentioning
confidence: 72%
“…Polyphenols have been widely used to improve the We found that the gavage of EGCG significantly increased the content of pyridoxal in the serum of the mice, thereby enhancing their ability to reduce the expression of IL-1β, TNF-α, IL-6 , and other pro-inflammatory factors while also enhancing the organisms’ immunity due to their good biological activity ( 25 27 ). Studies have shown that polyphenols, including EGCG and theaflavin-3′-O-gallate (TF3′G), are absorbed in the jejunum after being ingested ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Epigallocatechin-3-gallate (EGCG), a major bioactive polyphenol in green tea, is known to suppress inflammation and oxidative stress [ 110 ]. Many studies have shown that EGCG has anti-inflammatory effects on chronic inflammatory diseases, such as neurodegenerative diseases and cancers, in a multifactorial manner [ 111 , 112 ]. It improves acetic acid-induced colitis by reducing oxidative stress by decreasing nitric oxide (NO) production, increasing superoxide dismutase (SOD) expression, and inhibiting the production of TNF-α and IFN-γ in rats [ 113 ].…”
Section: Phytochemicals Targeting the Jak–stat Pathwaymentioning
confidence: 99%